2019
DOI: 10.1007/s12195-019-00585-0
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Biomechanical Responses are Dependent on Both Fluid Shear Stress and Tensile Strain

Abstract: Associate Editor William H. Guilford oversaw the review of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 85 publications
2
21
0
Order By: Relevance
“…As the diaphragm contracts, a negative intrapleural pressure expands the lungs. Concurrent fluid shear stress and tensile strain have been shown to influence cell area, PECAM‐1 phosphorylation, and ICAM‐1 expression 48 . CEC and LEC response to shear stress was also significantly regulated by the type of coating used.…”
Section: Discussionmentioning
confidence: 99%
“…As the diaphragm contracts, a negative intrapleural pressure expands the lungs. Concurrent fluid shear stress and tensile strain have been shown to influence cell area, PECAM‐1 phosphorylation, and ICAM‐1 expression 48 . CEC and LEC response to shear stress was also significantly regulated by the type of coating used.…”
Section: Discussionmentioning
confidence: 99%
“…As an efficient signaling molecule, PECAM-1 has diverse vascular biology roles, including angiogenesis, platelet function, thrombosis, mechanosensing of fluid shear stress, and regulating leukocyte migration ( Woodfin et al, 2007 ). Five percent CS alone did not cause any significant changes in cell area and cell aspect ratio compared to untreated control cells, but cell area increased significantly in response to concurrent shear stress and CS ( Meza et al, 2019 ). Upon CS, the cytoplasmic domain of PECAM-1 is unfolded and exposes a phosphorylation site, allowing the rapid PECAM-1 phosphorylation, transforming a mechanical signal into a biochemical signal ( Snyder et al, 2017 ).…”
Section: Dysfunction Of Pulmonary Microvascular Endothelial Barriermentioning
confidence: 90%
“…These findings underline that mechanotransduction depends on a complex interplay of diverse forces. Meza et al [ 43 ] also analyzed the effects of pulsatile shear stress and cyclic tensile strain on ECs and found that both forces, but not synergistically, increased effects on EC morphology and activation, indicated by the phosphorylation of platelet endothelial cell adhesion molecule (PECAM)-1 and increased surface expression of ICAM-1.…”
Section: In Vitro Systems To Model Flow Dynamics and Endothelial Wall Shear Stress (Wss)mentioning
confidence: 99%